Pollen and nutlet micromorphology of a rare species Salvia kurdica (Lamiaceae) from Turkey - Firat, Mehmet; Başer, Birol; Aziret, Akin (Pakistan Botanical Society, 2017)
Salvia kurdica Boss & Hohen. ex. Benth. is known from only 2 localities in the territory of southeastern Turkey and northern Iraq. As a part of the fieldwork, this species was collected from Şırnak Province. In this study, the micromorphological characteristics of its pollen grains and nutlets have been investigated using scanning electron microscopy and a light microscope. The pollen grains are hexacolpate, radially symmetrical, isopolar, and suboblate. Its exine sculpturing is bireticulate-perforate. The nutlets are rounded-trigonous in transverse sections, orbicular ovate-oblong in shape, glabrous and slightly tuberculate. This is an invasive species in Turkey. © 2017, Pakistan Botanical Society. All rights reserved.
Keywords: Morphology; Nutlet; Pollen; Salvia kurdica; Turkey